2017
DOI: 10.3390/nu9111237
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fermentation Patterns of Rice Bran Components by Human Gut Microbiota

Abstract: Whole grain rice is a rich source of fiber, nutrients, and phytochemicals that may promote gastrointestinal health, but such beneficial components are typically removed with the bran during polishing. Soluble feruloylated arabinoxylan oligosaccharides (FAXO) and polyphenols (RBPP) isolated from rice bran are hypothesized to have positive impacts on human gut microbiota through a prebiotic function. Using an in vitro human fecal fermentation bioassay, FAXO and RBPP treatments were assessed for short-chain fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 58 publications
5
29
0
Order By: Relevance
“…In another study, intake of rice bran for 14 days was shown to result in a decreased ratio of the intestinal abundance of Firmicutes and Bacteroidetes (decreased Firmicutes–Bacteroidetes ratio), as well as an increased production of some health-promoting SCFAs such as acetate, among American CRC survivors [ 77 ]. This is consistent with the recent finding that the intake of feruloylated arabinoxylan oligosaccharides, a carbohydrate contained in rice bran [ 78 ], would lead to an elevation in the intestinal production of SCFAs including butyrate and propionate [ 79 ]. These SCFAs were previously suggested to exhibit cancer-preventive properties [ 17 ].…”
Section: Evidence For the Link Between Intestinal Microbiota And Csupporting
confidence: 92%
“…In another study, intake of rice bran for 14 days was shown to result in a decreased ratio of the intestinal abundance of Firmicutes and Bacteroidetes (decreased Firmicutes–Bacteroidetes ratio), as well as an increased production of some health-promoting SCFAs such as acetate, among American CRC survivors [ 77 ]. This is consistent with the recent finding that the intake of feruloylated arabinoxylan oligosaccharides, a carbohydrate contained in rice bran [ 78 ], would lead to an elevation in the intestinal production of SCFAs including butyrate and propionate [ 79 ]. These SCFAs were previously suggested to exhibit cancer-preventive properties [ 17 ].…”
Section: Evidence For the Link Between Intestinal Microbiota And Csupporting
confidence: 92%
“…Apart from the production of SCFAs from fermentation, prebiotics are expected to have the capacity to selectively promote the growth and/or activity of gut bacteria involved in health and well-being (Pham et al, 2017). Changes in the community composition due to the ingestion of dietary fibers occur as a result of differences in their physicochemical and metabolic properties (Umu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with prebiotics might be a promising method that could confer positive health benefits in aquatic animals, including cultured crustaceans (Daniels et al, 2013;Chen et al, 2017;Duan et al, 2017;Elshopakey et al, 2018;Safari and Paolucci, 2018). In vitro anaerobic fermentation studies provide a primary approach for initial evaluation of the positive benefits of compounds through their effects on metabolic activities of gut microbiota (Pham et al, 2017). Many research efforts aimed at assessing the impacts of potential prebiotics on the dynamics of human gut microbiota have applied in vitro fermentation approaches (Scott et al, 2014;Pham et al, 2017;Sato et al, 2017;Baxter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the solid beverage produced from rice bran nutrients and rice bran nutrition fiber has a rich cocoa flavor and a favorite rich moisturizing taste. The eater supplements the daily protein, unsaturated fatty acids, vitamins, minerals, etc., and can also supplement the dietary fiber to obtain a smooth and laxative health care function [46]. The rice bran nutrient solid beverage and the rice bran nutrient fiber solid beverage have pure natural and low price.…”
Section: Rice Bran Nutrients and Nutrient Fibermentioning
confidence: 99%